Recurring patterns in bacterioplankton dynamics during coastal spring algae blooms - Hanno Teeling; Bernhard M Fuchs; Christin M Bennke; Karen Krüger; Meghan Chafee; Lennart Kappelmann; Greta Reintjes; Jost Waldmann; Christian Quast; Frank Oliver Glöckner; Judith Lucas; Antje Wichels; et al. (eLife, 2016)
A process of global importance in carbon cycling is the remineralization of algae biomass by heterotrophic bacteria, most notably during massive marine algae blooms. Such blooms can trigger secondary blooms of planktonic bacteria that consist of swift successions of distinct bacterial clades, most prominently members of the Flavobacteriia, Gammaproteobacteria and the alphaproteobacterial Roseobacter clade. We investigated such successions during spring phytoplankton blooms in the southern North Sea (German Bight) for four consecutive years. Dense sampling and high-resolution taxonomic analyses allowed the detection of recurring patterns down to the genus level. Metagenome analyses also revealed recurrent patterns at the functional level, in particular with respect to algal polysaccharide degradation genes. We, therefore, hypothesize that even though there is substantial inter-annual variation between spring phytoplankton blooms, the accompanying succession of bacterial clades is largely governed by deterministic principles such as substrate-induced forcing.